Sustaining incomes from non timber forest products: introduction and synthesis - Jong, W. de; Campbell, Bruce M.; Schroder, J.M. (2000)
Reasons for the decline of people’s income from any given non-timber forest product are: over-harvesting of the resource base; capturing of the business by local elite; domestication of the product; decreased demand; or manufacturing of substitutes. In all of these scenarios, income for local collectors is likely to diminish or disappear altogether. This Special Issue of the International Tree Crops Journal brings together a number of studies from Bolivia, Peru, Zimbabwe and Cameroon assessing the sustainability of incomes from non-timber forest products once their commercialisation has already been achieved. The studies conclude that avoiding over-harvesting of a commercially successful forest product will in most cases require some restraints on harvesting, usually through developing rules and regulations at the appropriate level. These institutional arrangements are also needed to avoid exclusive income capturing by powerful elites. Sustained production can also be achieved through intensified management or cultivation. Maintaining market demand requires constant marketing effort, or adjusting the products supplied to different demands. Even so, there is always the possibility that others that provide a higher consumer satisfaction or are produced more efficiently will replace commercially successful forest products. A constant effort is thus needed to develop new products, for which the entire production-marketing may have to be set up.